2023
DOI: 10.3390/v15061366
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Geometry and Dynamics of Viral Structures: A Review of Computational Approaches Based on Alpha Shape Theory, Normal Mode Analysis, and Poisson–Boltzmann Theories

Abstract: The current SARS-CoV-2 pandemic highlights our fragility when we are exposed to emergent viruses either directly or through zoonotic diseases. Fortunately, our knowledge of the biology of those viruses is improving. In particular, we have more and more structural information on virions, i.e., the infective form of a virus that includes its genomic material and surrounding protective capsid, and on their gene products. It is important to have methods that enable the analyses of structural information on such la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 200 publications
0
0
0
Order By: Relevance
“…Recently, the structure of viruses where electrostatic interactions play an important role received increasing attention. The review [77] describes recent advances in understanding viral structures. Biophysics puts forward questions which are sometimes raised in the surfactant community regarding short-distance electrostatics, typically close to an interface [42,78] or dense charged media [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the structure of viruses where electrostatic interactions play an important role received increasing attention. The review [77] describes recent advances in understanding viral structures. Biophysics puts forward questions which are sometimes raised in the surfactant community regarding short-distance electrostatics, typically close to an interface [42,78] or dense charged media [55].…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this problem, more terms are needed in the energy. The Go Model has been parametrized with this purpose in mind, including terms that are based on bond lengths, torsion angles, dihedral angles, and a van-der-Waals-like term ( 16 , 17 ). Note that the Go model only considers CA atoms and currently works only for proteins.…”
Section: Description Of the Web Servermentioning
confidence: 99%
“…First, it allows to define the neighbours in the pairwise sums of the energy function using Delaunay triangulation ( 15 ), and second, it provides the option of using a Go-like model to define the potential in proteins ( 16 ). It has been shown that the use of such potential reduces the number of covalent bonds with unreasonable stereochemistry during the transition ( 17 ). The code has been entirely rewritten to enable the study of very large systems and the web interface now offers a user-friendly visualization of the resulting trajectory in the output.…”
Section: Introductionmentioning
confidence: 99%